SEBARAN SPASIAL TUMBUHAN OBAT YANG DIMANFAATKAN MASYARAKAT KAMPUNG NYUNGCUNG, DESA MALASARI, KECAMATAN NANGGUNG, KABUPATEN BOGOR - Siti Nurjannah; Ervizal A.M. Zuhud; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Nyungcung Kampoong is least developed village, located in Nanggung sub-district. The community of the kampoong utilized medicinal plant from its sorrounding location included forest area. For the purposes of management, spatial distribution mapping of medicinal plant is very important. The purpose of the study is to identify the diversity and forms of utilization as well as biophysical characteristics and accessibility. Data collection, interview and field observation were conducted in March 2015 in Nyungcung Kampoong, Village Malasari, Nanggung sub-district, Bogor. Result showed that there were 140 species of medicinal plants utilized by the community. Among the medicinal plants species family Zingiberaceae was the most predominantly utilized located in home garden and upland field. The average distance medicinal plants from the house was about 214 meters located on 600–800 meters above sea level, with flat slope. Community utilized medicinal plants that located at its surrounding house. This is due to the fact that they have conducted domestication of the wild species from the forest. This showed that community contribute to forests conservation. Keywords: distribution, medicinal plant, utilization